Collaborative Evaluations: Step-by-Step - Connie Walker-Egea (Journal of MultiDisciplinary Evaluation)
A review of the book Collaborative Evaluations: Step-by-Step (2nd ed.)by Liliana Rodríguez-Campos and Rigoberto Rincones-Gómez, published in 2013 by Stanford University Press.